How : why how we do anything means everything-- in business (and in life) - Seidman, Dov (John Wiley & Sons, 2007)
The flood of information and unprecedented transparency reshaping today's business world has dramatically changed the rules of the game. It's no longer what you do that sets you apart from others, but how you do what you do. Whats are commodities, easily duplicated or reverse-engineered.